2015
DOI: 10.1111/1471-0528.13541
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic myoma after laparoscopic morcellation: a systematic review of the literature

Abstract: Background Laparoscopic morcellation is frequently used for tissue removal after laparoscopic hysterectomy or myomectomy and may result in parasitic myomas, due to seeding of remained tissue fragments in the abdominal cavity. However, little is known about the incidence and risk factors of this phenomenon.Objectives To identify the incidence and risk factors for the development of parasitic myoma after laparoscopic morcellation.Search strategy A systematic review of the literature in Pubmed (MEDLINE) and Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 46 publications
1
86
1
Order By: Relevance
“…A study by Van Der Meulen et al identified 69 patients who developed new, parasitic myomas resulting from morcellation. The risk for such complication has been estimated at 0.1-0.9% [34]. Other authors emphasize the possibility of spreading previously undiagnosed sarcoma or endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Van Der Meulen et al identified 69 patients who developed new, parasitic myomas resulting from morcellation. The risk for such complication has been estimated at 0.1-0.9% [34]. Other authors emphasize the possibility of spreading previously undiagnosed sarcoma or endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 This rate is much higher than the prevalence of uterine sarcoma, the focus of the U.S. Food and Drug Administration's statement discouraging the use of laparoscopic power morcellators in 2014. 13 New techniques have emerged to improve the safety of tissue extraction including manual or power morcellation within a containment bag.…”
Section: Published Case Reports Of Parasitic Leiomyomas Occurring Folmentioning
confidence: 99%
“…1 Although little is known about the incidence and risk factors of this condition, it is presumed to originate from pedunculated fibroids that spontaneously detach from the uterus and obtain an alternative blood supply from adjacent organs. 2,5 In recent decades, however, an increase in the development and use of minimally invasive techniques has led to a potential iatrogenic origin of parasitic leiomyoma. The inadvertent dissemination of tissue fragments during laparoscopic surgical maneuvers, tissue manipulation, and extraction procedures creates the potential for fibroids to parasitize to extrauterine sites.…”
Section: Introductionmentioning
confidence: 99%
“…PMs largely occurred in the dependent part of the abdominal cavity, including intestines, peritoneum, omentum and port sites, and received abundant blood supply [8,[10][11][12][13][14][15][16][17]. Most women (78.3 %) presented with symptoms, such as abdominal or pelvic pain, dyspareunia, abdominal distension, abdominal pressure, urinary frequency and constipation [13,14,[17][18][19][20][21][22][23]. In 10.1 % patients, debulking procedure, such as omentectomy, appendectomy, or bowel resection, was necessary to eliminate all PMs [18,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Most women (78.3 %) presented with symptoms, such as abdominal or pelvic pain, dyspareunia, abdominal distension, abdominal pressure, urinary frequency and constipation [13,14,[17][18][19][20][21][22][23]. In 10.1 % patients, debulking procedure, such as omentectomy, appendectomy, or bowel resection, was necessary to eliminate all PMs [18,24,25]. Thus, it is important to elucidate the pathophysiology of laparoscopic morcellator-induced PMs.…”
Section: Introductionmentioning
confidence: 99%